MO059: Trajectory Analysis of the Kidney Organoid Proteome Extends its Modelling Potential of Disease. (3rd May 2022) - Lassé, Moritz; Bonin, Léna L; El Saghir, Jamal; Eddy, Sean F; Hutzfeldt, Arvid; Hoxha, Elion; Dumoulin, Bernhard; Lindenmeyer, Maja; Schlüter, Hartmut; Beck, Bodo B; Brandts, Paul; Kretzler, Matthias; et al.
Abstract: BACKGROUND AND AIMS: Kidney organoids are a valuable and innovative model to understand genetic diseases, kidney development and transcriptomic dynamics. However, their proteome has not been analyzed so far. It is unclear how their proteome changes during differentiation, and if more complex disease processes such as inflammatory tissue responses could be modelled with this approach. METHOD: Here, we used proteomics to compare organoids with existing model systems such as native glomeruli and cultured cells. We characterize the trajectory of organoid differentiation and delineate innate immune responses in organoids to expand its scope as a model system in nephrology. We also compared our proteomics with bulk and single cell transcriptomic data. RESULTS: Genes involved in podocytopathies and cystic kidney diseases were abundantly expressed on protein level, distinguishing organoids from almost every available cell culture model. On their pathway to terminal differentiation, organoids developed increased deposition of extracellular matrix. Single cell transcriptomic analysis suggests that most changes locate to podocytes and early podocyte progenitors. This matrix deposition is different from commonly used animal models of glomerular disease. A novel signaling system discovered was the TNFα system, a system also available in podocytes. Incubation of organoids with high concentrations of TNFα led to an activation of NF-kB signaling, and secretion of cytokines and complement components, alongside with extracellular matrix components. CONCLUSION: Interestingly, this signaling system directly links inflammatory signaling, production of cytokines and complement, and production of extracellular matrix. Thus, we provide a repository of human kidney organoid proteins that revealed the potential to model pathophysiological pathways beyond genetic diseases.